Factors that influence the survival of Post-Covid Tourism in Kuala Lumpur / Nor Najmi Aideel Nor Azizi and Siti Fatimah Zahraa Jamal - Nor Azizi, Nor Najmi Aideel; Jamal, Siti Fatimah Zahraa (2022)
The purpose of this study was to look into the elements that determine the survival of post-Covid tourism in Kuala Lumpur. Tourist Intention to Travel, Government Regulation, Airline Operation, and Hotel Operation were the factors observed in this study. This study employed a convenience sampling strategy, with 110 respondents drawn from the general public in and around Kuala Lumpur. The quantitative research approach was used by the researchers in this study to determine which elements influence the survival of post-Covid tourism in Kuala Lumpur. Pearson's correlation was utilised to investigate the link between the elements influencing post-Covid tourism survival in Kuala Lumpur. These research papers go into greater detail by employing particular analysis in SPSS version 28. Finally, the study's findings revealed that just tourist intention to travel had no association with the survival of post-Covid tourism in Kuala Lumpur. Meanwhile, government regulation, airline operations, and hotel operations all appeared to have a substantial impact on the survival of post-Covid tourism in Kuala Lumpur. As a result, the government's response to the Covid-19 is critical to the sustainability of post-Covid tourism in Kuala Lumpur.